Schools that learn : a fifth discipline fieldbook for educators, parents, and everyone who cares about education - Cambron, Nelda; Mccabe; Kleiner, Art.; Dutton, Janis; Lucas, Timothy; Smith, Bryan (London : Nicholas brealey publshing., 2003)
Peter Senge's national bestseller, The Fifth Discipline, revolutionized the practice of management by introducing the theory of learning organizations. Now Dr. Senge moves from the philosophical to the practical by answering the first question all lovers of the learning organization ask: What do they do on Monday morning? The fieldbook is an immensely pragmatic guide. It shows how to create an organization of learners where memories are brought to life, where collaboration is the lifeblood of every endeavor, and where the tough questions are fearlessly asked. The stories in this book show that companies, businesses, schools, agencies, and even communities can undo their learning disabilities and achieve superior performance. If ever a book gave meaning to the phrase 'hands-on, ' this is it. Senge and his four co-authors cover it all: reinventing relationships, being loyal to the truth, strategies for developing personal mastery, building a shared vision, systems thinking in an organization, designing a dialogue session, strategies for team learning, organizations as communities, and designing an organization's governing ideas.
Includes bibliographical references and index.
Keywords: School improvement programs -- United States; Organizational learning -- United States